Perancangan Website Interaktif Ayam Penyet Nabila Berbasis Multimedia Untuk Meningkatkan Pengalaman Pelanggan - Devita Prisilla Maharani; Ricky Ramadhan Harahap; Supiyandi (Jurnal Nasional Teknologi Komputer, 2026)
The development of information and communication technology has encouraged culinary business operators to utilize digital media as a means of promotion and customer service. Ayam Penyet Nabila, as one of the culinary businesses, still requires an information medium capable of presenting information in an engaging and interactive manner. This study aims to design and develop a multimedia-based interactive website for Ayam Penyet Nabila to enhance the customer experience. The methods used in designing the website include needs analysis, system design, interface design, implementation, and testing. The website is developed by utilizing multimedia elements such as text, images, animations, audio, and video to present menu information, business profiles, location details, and interactive features that facilitate customer interaction. The results of this study indicate that the interactive website is able to deliver informative and engaging content, increase customer interest, and strengthen the digital image of Ayam Penyet Nabila. Based on testing results, the developed website functions properly and provides an improved user experience.